Projektpedagógia az angol mint idegen nyelv oktatásában 21. századi kompetenciákat támogató metodika mint az inklúzió hatékony terepe - Schnell, Zsuzsanna; Fóti, Nóra; Kochné Süli, Andrea (Kultúratudományi Szemle, 2022)
The project method in ESL teaching – a method supporting 21st century competencies as a platform for inclusion in the classroom Zsuzsanna Schnell– Nóra Fóti– Andrea Kochné Süli The present study gives an overview of the basic notions of Project Pedagogy as a method in rebirth in modern educational approaches. Defining the major principles and its connections to reform pedagogical perspectives and the RJR model of acquisition, we highlight how the Project method is particularly suited for ESL (English as a Second Language) teaching, in learning and understanding foreign languages and cultures. We delineate a representative example of Project methodology in the ESL classroom by providing a synopsis of the English program’s project in Deák Elementary School of the University of Pécs, a partner institute of the University of Pécs and our Faculty. The ZOOm-in-Project is a concrete example of project pedagogy and its creative fruitful application in the foreign language classroom. We also provide the exact steps, parts, phases of the project with important notes on potential pitfalls and future corollaries.